Miracles on the Border : Retablos of Mexican Migrants to the United States - Durand, Jorge (Book collections on Project MUSE., 1995)
Few forms of religious folk art are as abundant or expressive as Mexican retablos - folk images painted on sheets of tin that are offered as votives of thanks to Christ or the Virgin Mary for a miracle granted or a favor bestowed. In this vivid study, Jorge Durand and Douglas Massey offer a multilayered analysis of retablos created by Mexican migrants to the United States. Richly illustrated with forty color photographs, this book will appeal to those interested in Mexican folk art and religious art, sociologists, and others seeking a fuller understanding of transnational migration. The authors first trace the history of retablos, which began in the early seventeenth century when the art form emerged in Mexico as a blend of European and Amerindian votive traditions. While placing the paintings in the context of international votive conventions, Durand and Massey also distinguish the purely artistic techniques that define retablos, detailing their strong influence on many of Mexico's leading nineteenth- and twentieth-century painters, most notably Frida Kahlo. As Mexican migrants began to head north into the United States from western Mexico, a contemporary center of votive supplication, they brought the retablo tradition with them. Durand and Massey study these retablos both as aesthetic texts and as social documents. They systematically analyze 124 contemporary retablo texts created by migrants and their families, scrutinizing the shifting subjects and themes that constitute a running record of the migrants' unique experiences. The result is a vivid work of synthesis that connects the history of an art form and a people, links two very different cultures, and allows a deeper understanding of a major twentieth-century theme - the drama of transnational migration.